Band point algorithms for measuring diffraction pattern parameters in laser ektacytometry of red blood cells. (April 2021) - Nikitin, S.Yu.; Ustinov, V.D.; Shishkin, S.D.
Abstract: We consider the issues of measuring the deformability of red blood cells by the method of laser diffractometry in shear flow (ektacytometry). The measurement procedure is optimised taking into account the finite resolution of the video recording system of the laser ektacytometer. An algorithm is proposed that allows one to determine with high accuracy the diffraction pattern parameters necessary for measuring the characteristics of the erythrocyte deformability distribution.